More than just counting eosinophils: proximal oesophageal involvement and subepithelial sclerosis are major diagnostic criteria for eosinophilic oesophagitis. Issue 7 (30th June 2010) - Lee, Stephen; de Boer, W Bastiaan; Naran, Anupam; Leslie, Connull; Raftopoulous, Spiro; Ee, Hooi; Kumarasinghe, M Priyanthi
Abstract : Background: According to American Gastroenterological Association Institute criteria, the diagnosis of eosinophilic oesophagitis (EOE) requires clinicopathological correlation. In the appropriate clinical context, a high eosinophil count (HEC, defined as ≥15/HPF) is considered pathological evidence of EOE. However, HEC may not always be identified in biopsies given its patchy distribution, and there may be histological overlap between EOE and gastro-oesophageal reflux disease (GORD) in the distal oesophagus. Aims: To evaluate the utility of subepithelial sclerosis and HEC in proximal oesophageal biopsies as additional diagnostic criteria. Methods: Cases between 2004 and 2008 with paired proximal and distal oesophageal biopsies and the mention of eosinophils in the reports were retrieved from PathWest Queen Elizabeth II Medical Centre archives. Biopsies were reviewed and assessed for eosinophilic count and presence of subepithelial stroma and sclerosis. A final diagnosis was made after review of both biopsy and clinical details. Results: There were 23 cases of EOE and 20 cases of GORD in an adult cohort. In comparison to GORD, cases of EOE had significantly higher eosinophil counts in proximal (39.4 vs 0.6 eosinophils/HPF) and distal biopsies (35.6 vs 1.9), with HEC in proximal biopsies a feature exclusive to EOE (83% vs 0%). Subepithelial sclerosis was identified in at least one biopsy in 74% of EOE and in only a single case of GORD. Conclusions: HEC in proximal oesophageal biopsies and subepithelial sclerosis should be considered major diagnostic findings in EOE.